A consensus approach to PI gains tuning for quality‐fair video delivery. (16th January 2017) - Dal Col, Laura; Tarbouriech, Sophie; Zaccarian, Luca; Kieffer, Michel
Summary: In this paper, we provide necessary and sufficient conditifor the quality‐fair delivery of multimedia contents to mobile users. We control the encoding rates and the transmission rates of the video streams, delivered through a limited capacity channel. This problem is cast into a problem of consensus among identical discrete‐time linear systems, connected through a network with fixed and fully connected topology. The information exchanged over the communication network is the measure of the quality of the encoded videos. Based on a consensus result for identical linear systems, we reduce the problem of designing the proportional and integral gains of the encoding rate and transmission rate controllers to a linear static output feedback. We propose an iterative design technique based on linear matrix inequalities to solve the corresponding nonconvex problem, thereby providing a constructive optimality‐based approach to the proportional and integral gains tuning problem. We demonstrate the effectiveness of our method in simulations, where we compare it with pre‐existing approaches. Copyright © 2017 John Wiley & Sons, Ltd.